3(4x-2)-(5x-8)=-(2x+3)

Simple and best practice solution for 3(4x-2)-(5x-8)=-(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-2)-(5x-8)=-(2x+3) equation:



3(4x-2)-(5x-8)=-(2x+3)
We move all terms to the left:
3(4x-2)-(5x-8)-(-(2x+3))=0
We multiply parentheses
12x-(5x-8)-(-(2x+3))-6=0
We get rid of parentheses
12x-5x-(-(2x+3))+8-6=0
We calculate terms in parentheses: -(-(2x+3)), so:
-(2x+3)
We get rid of parentheses
-2x-3
Back to the equation:
-(-2x-3)
We add all the numbers together, and all the variables
7x-(-2x-3)+2=0
We get rid of parentheses
7x+2x+3+2=0
We add all the numbers together, and all the variables
9x+5=0
We move all terms containing x to the left, all other terms to the right
9x=-5
x=-5/9
x=-5/9

You can always share this solution

See similar equations:

| 3d-105=120 | | 6(4x7)=282 | | 2x+2=3-× | | 9x+5=19x | | x/x=100/110 | | x+2=5(2x+4) | | x+2=5(2x=4) | | 8y+1=-71 | | 18+24=7c | | 9x-34/8=7 | | 15+3b=36 | | x=2=5(2x=4) | | -12+6=2t | | 7x+11x=206 | | 73+69+(9x+2)=180 | | 91+47+(6+6x)=180 | | 91+47+96+6x)=180 | | 4-9x-15=11x-29+4x | | 3×-3=-2x+8 | | T=3.5x8.5+5 | | 9=10-1/2x | | 10=10-1/2x | | 15x-90=54-6x | | 3(p–2)=18 | | 180-2x+x+13+62=180 | | K+5-1=k-5 | | 4(x+3)=3x+8 | | 14x+17x+19x+50=950 | | 3y-5=4y-6 | | 9n+1=+100 | | 9n+1=+00 | | 12x+14=-10-2x |

Equations solver categories